PROBLEMS OF IMPLEMENTING INTERNATIONAL EDUCATIONAL STANDARDS IN THE SYSTEM OF PROFESSIONAL EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the problems of modernization of the vocational education system in the Republic of Uzbekistan, the introduction of international educational standards in vocational education.